2022
DOI: 10.3389/fcvm.2022.854501
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Plasma Galectin-3 in Heart Failure With Preserved Ejection Fraction: A Meta-Analysis

Abstract: BackgroundHeart failure with preserved ejection fraction (HFpEF) is an increasing public health concern. Currently, data regarding the clinical application value of plasma Galectin-3 (Gal-3) in HFpEF are contradictory. Therefore, we performed the following meta-analysis to appraise the clinical implications of serum Gal-3 in HFpEF, including its capacity to predict new-onset disease, long-term unfavorable endpoints, and the degree of cardiac structural abnormality and left ventricular diastolic dysfunction (LV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 62 publications
1
7
0
1
Order By: Relevance
“…In the present study, plasma galectin-3 levels were markedly increased in HF than in the controls. Similar results were reported by Shi Y et al [12] and Jiang J et al [13]. Further, in this study, the levels of galectin-3 increased significantly as age increased.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, plasma galectin-3 levels were markedly increased in HF than in the controls. Similar results were reported by Shi Y et al [12] and Jiang J et al [13]. Further, in this study, the levels of galectin-3 increased significantly as age increased.…”
Section: Discussionsupporting
confidence: 92%
“…Galectin-3, a soluble β-galactoside-binding lectin involved in cell proliferation, adhesion, migration and apoptosis, appears to promote inflammation or tissue fibrosis. Over the past decades, the prognostic role of serum galectin-3 as a biomarker linking oxidative stress, inflammation and fibrosis has been demonstrated in many pathological conditions such as HF, atherosclerosis, CKD and cancer 5 , 20 22 . Especially in patients with CKD, a recent large meta-analysis of 5226 patients showed that high galectin-3 levels were associated with an increased risk of all-cause mortality and CV events 10 .…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies, such as the one conducted by de Boer et al, showed that the prognostic value of Gal-3 stands out only in those patients with HF and preserved left ventricular ejection fraction (LVEF) [ 44 ]. One meta-analysis claimed that Gal-3 can be used as a predictor for new-onset HF with preserved LVEF, which also correlates with left ventricular diastolic dysfunction [ 45 ]. A recent review article confirmed these findings and proposed Gal-3 as a marker that can guide the therapeutic approach in HF with preserved LVEF [ 46 ].…”
Section: Gal-3 and Cardiac Remodelingmentioning
confidence: 99%